BUMDes Peran Badan Usaha Milik Desa (Bumdes) Sepakat Jaya Mandiri Dalam Meningkatkan Kesejahteraan Masyarakat Di Gampong Tingkeum Manyang Kecamatan Kutablang Kabupaten - Rizka, Siti Nura; Rusna, Rusnawati (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
Community welfare is a condition that causes people to feel safe, prosperous and safe and free from all kinds of disturbances and difficulties. One way to improve community welfare is through the existence of Village-Owned Enterprises (BUMDes). BUMDes is a business entity whose capital is wholly or largely owned by the village directly through participation in village assets, which are allocated for the management of goods, services and other commercial activities for the welfare of the village community. BUMDeas also aims to increase the village's original income. To find out how BUMDes improve the welfare of the people of Gampong Tingkeum Manyang, Kutablang District, Bireuen Regency, research was conducted with the title